A New Approach for Analyzing Stock Market Stress Based on the Warsaw Stock Exchange in 2005–2019. Issue 4 (4th July 2021) - Kosiorowski, Daniel; Rydlewski, Jerzy P.; Klecha, Tadeusz; Mielczarek, Dominik
ABSTRACT: In this paper, we propose the use of a novel approach for measuring stresses in capital. Our proposal relies on a framework offered by the statistical theory of shape. We describe a stress function based on the concept of a mean shape determined by representative particles of a capital carrier as well as changes in the amount and structure of stresses in capital, employing, among others, Bookstein's pair of thin plain spline deformation, and a measurement of shape variability. We propose a robust approach for estimating the stress functional based on the concept of data depth.